The Schüssel Era in Austria - Bischof, Günter (Contemporary Austrian Studies, 2009)
Wolfgang Schüssel was a dominating actor in the Austrian political arena over a period of twenty years. He served as minister of economics (1989-1995), and vice chancellor and foreign minister (1995-2000) in ÖVP/SPÖ grand coalition governments. As chairman of the ÖVP (1995-2007), he brought his conservative party out of the political wilderness of opposition and playing junior partner in coalitions with the SPÖ. He dominated Austrian politics as chancellor (2000-2007) in a small coalition with Jörg Haider's controversial aggressively nationalist FPÖ. Schüssel tried to domesticate the Freedomites by holding them on a tight leash in his coalition government. He needed the FPÖ to accomplish his neoliberal economic and social reform agenda, while at the same time the FPÖ undermined Schüssel's EU policies. The essays in this volume argue that Schüssel's political record and legacy are ambiguous. With a confrontational style of governance he unleashed big reforms such as trimming the hidebound pension system and giving more autonomy to higher education. In the process he undermined Austria's consensual social partnership. His record of supporting the European Union agenda is ambivalent. Austrian public opinion in support of the EU declined precipitously. He was a superb tactician and negotiator yet failed to achieve broad popular acceptance for his ambitious reforms. His imprint on Austrian history is so significant that many of the authors of the essays in this volume call it "the Schüssel era."